PELATIHAN SENAM AYO BANGKIT LEBIH MENINGKATKAN KEBUGARAN FISIK DITINJAU DARI DAYA TAHAN UMUM DARIPADA SENAM AYO BERSATU SERI 2 PADA MAHASISWI JURUSAN KEBIDANAN POLITEKNIK KESEHATAN DENPASAR - I Nyoman Nuada; Ketut Tirtayasa; J Alex Pangkahila (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2014)
Physical fitness is very important to facilitate a person perform daily activities without causing significant fatigue . In an effort to improve the physical fitness training needs to be implemented and measured regularly.The purpose of this study is to determine the improvement of physical fitness in terms of general endurance, the training Gymnastics Gymnastics Ayo Bangkit and Ayo Bersatu Series. The sample is students at Midwifery Department in Polytechnic of Health, Ministry of Health with an average age of 18 years . This study is a randomized experimental design with pretest - posttest control group design with a total sample of 11 people in each group . Samples were selected , respectively then each group was given training exercises . Treatment 1 (P1) given training and treatment of Gymnastics Ayo Bangkit while treatment 2 (P2) was given training of Gymnastics Ayo Bersatu Series 2 . Training conducted for 8 weeks with a frequency of 3 times a week starting at 17:00 to 18:00 pm located in the campus of Midwifery Department of Polytechnic of Health, Ministry of Health Denpasar. The results of computer-assisted analysis showed a significant decrease in the time of aerobic run 2.4 km at (p < 0.05) for both groups of gymnastics , and also an increase in the pulse rate at the end of exercise treatment in both groups . Ayo Bangkit Gymnastics group increased pulse rate by 11 % and the group of Ayo Bersatu Gymnastics Series 2 by 6 % . Besides occurring differences training increased pulse rate significantly (p < 0.05) . Results of statistical analysis of differences in the time of aerobic run 2.4 miles in P1 and P2 is 42 % and the difference in pulse rate of P1 reaches training zone while P2 is not at the training zone . P1 does not get to the training zone .